Implementing organizational ambidexterity using the balanced scorecard in Puebla City's hotel industry, Mexico - Lastre Sierra, Hassir; Ruiz-Molina, Antonio; Barrón Villaverde, Diana (Emerald, 2024)
This paper investigates the effectiveness of the Ambidextrous Scorecard (ASC) in facilitating the integration of organizational ambidexterity in four-star Puebla City hotels for managing exploitation and exploration activities. It proposes an integrated approach to ambidexterity and introduces the ASC as a tool explicitly targeting hotels’ challenges and opportunities.
Keywords: Planificación estratégica; Hostelería; Organizational ambidexterity; Balanced scorecard; Exploitation; Exploration; Strategic management; Efficiency; Innovation; Hotel industry